The nitrogen relationships of maize/bean associations - Saito, Siu Mui Tsai (International Center for Tropical Agriculture, 1982)
Intercropping of maize and beans is practiced widely throughout the tropical and subtropical regions of Latin America, particularly among small farmers with limited technical resources. This paper reviews how association affects the nitrogen (N) balance of legumes and nonlegumes, paying particular attention to N2 fixation and N transfer.